Hate crimes, the hate speech phenomenon, practice of the European Court of Human Rights and the Russian approach to determining extremist activity - Vyacheslav V. Koryakovtsev; Xenia V. Pitulko; Anzhelika A. Sergeeva (Правоприменение, 2020)
The subject of the research is criminal law rules that provide for criminal liability for hate crimes and the judicial decisions of the European Court of Human Rights on hate crimes.The purpose of the article is to confirm or refute the hypothesis that a unified approach to the definition of the legal concept of hate speech and the limits of its application is necessary. This approach must be based on the legal positions of the European Court of Human RightsThe research methodology includes analysis and interpretation of court decisions of the European Court of Human Rights, as well as a dialectical approach to the analysis of various points of view to the definition of extremist activity.The main results and scope of their application. The relevance of the research proposed for publication is due to the lack of uniform practice of applying the articles of the Russian Criminal Code on so-called "hate crimes" by Russian courts and the presence of significant contradictions in the positions of the European Court of Human Rights and the state position of the Russian Federation in defining key concepts in this area that are extremely important for criminal procedure and administrative activities. The paper considers scientific and practical attempts to define "hate crimes" in the global and regional human rights systems, basic recommendations of the UN on countering such crimes, and offers an interpretation of the term hate speech in relation to the related criminological concept of hate crime. The text provides statistical data describing the level of such crime and the practice of the ECHR in this area, mentions a list of criteria according to which" hate crimes " can be motivated by language differences, gender, sexual orientation and other characteristics, as well as criteria that distinguish hate speech from freedom of expression, and suggests decriminalization of part 1 of article 282 of the Russian Criminal Code.Conclusions. It is necessary to unify the concepts of "hate crimes" (and the practice of their application) in the direction of, in particular, reducing the number of decisions of the European Court of Human Rights against the Russian Federation and increasing the level of legal protection of both the individual citizen of the Russian Federation and freedom of speech and expression.